Expressing and Practicing Emotions. Towards an Emotional Dimension of Diego Portales. Chile, 1821-1837 - Sadarangani Leiva, Javier (Revista de Historia Social y de las Mentalidades, 2023)
This paper aims to recognise, characterise and analyse the emotional dimension of one of the most paradigmatic historical and historiographical figures in Chilean history: Diego Portales. Using his epistolary as the main document and the history of emotions as a scheme of analysis, our interest is to learn more about the expressive repertoires and emotional practices that shaped the ways of feeling in early nineteenth-century Chile by a specific social sector. As a hypothesis, we argue that the expression of emotions and emotional practices were abundant and central in the writing of this figure, which challenge our conception of mainly logical or rational historical subjects, according to modern terms. KEY WORDS: Diego Portales; History of emotions; Chile; Nineteenth century.
Keywords: Diego Portales; History of emotions; Chile; Nineteenth century